Two control strategies for semi-active load path redistribution in a load-bearing structure. (1st March 2019) - Gehb, Christopher M.; Platz, Roland; Melz, Tobias
Highlights: Numerical and experimental investigation of load path redistribution. Controlled semi-active guidance elements with friction brakes. Semi-active guidance elements providing an additional load path. Two control strategies are designed and compared to redistribute the load path. Numerical modeling of a load-bearing structure with nonlinear LuGre friction model. Abstract: In this paper, a two mass oscillator, a translatoric moving mass connected to a rigid beam by a spring-damper system, is used to numerically and experimentally investigate the capability of load path redistribution due to controlled semi-active guidance elements with friction brakes. The mathematical friction model will be derived by the Lu Gre approach. The rigid beam is embedded on two supports and is initially aligned with evenly distributed loads in beam and supports by the same stiffness condition. With the semi-active auxiliary guidance elements it is possible to provide additional forces to relieve one of the beam's supports. Two control strategies are designed and tested to induce additional forces in the auxiliary guidance elements to bypass a proportion of loading away from the spring-damper system towards the now kinetic auxiliary guidance elements. The control strategies I and II depend on the different control inputs: I beam misalignment and II desired reaction force ratio in the supports. The beam's misalignment and the supports' reaction forces are calculated numerically and measured experimentally for varying stiffness parameters of the supports and are compared with and without semi-active auxiliary kinematic guidance elements. The structure's moving mass is loaded with a force according to a step-function. Thus, undesired misalignment caused by varying stiffness as well as undesired load distribution in the structure's supports can be reduced by redistributing load between the supports during operation.